Peningkatan Akses dan Kualitas Air Minum melalui Perbaikan Sarana SPAM di Desa Lembengan Kecamatan Ledokombo - Jember (Universitas Negeri Padang, 2021)
The goal of PKMS is to improve access and quality of drinking water through improvements to infrastructure / SPAM facilities in the context of sustainable use of built drinking water facilities. The problems faced by partners are: 1). SPAM facilities are not functioning properly because there are still leaks in the broncaptering, collection wells, water towers and pipelines; 2). The low level of public awareness of clean and healthy living habits (PHBS) by bathing, washing and defecating in water bodies, namely rivers and springs, can reduce the quality of drinking water raw water; 3). The absence of a structured organization that specifically manages the SPAM infrastructure built at the village level, so as to ensure sustainability and increase access to drinking water up to 100%.The approach used in the community service activities of the PKMS scheme is an individual and classical approach using interviews. The output of this PKMS is the publication of articles in the Journal of Community Service (accredited by Sinta S5). This program is expected to be able to facilitate the functioning of rural SPAM infrastructure facilities in order to improve access and quality of drinking water which can support the 6th SDGs (Sustainable Development Goals) goal of achieving universal access in the drinking water and sanitation sector by 2030, and then be able to provide a multiplier. effect for partners and other SPAM managers in Jember Regency. Especially to improve the performance of KP-SPAMS as the manager of rural SPAM so that it becomes more credible as a public service institution.